Behavioral effects of endogenous or exogenous estradiol and progesterone on cocaine sensitization in female rats - Souza, M.F. (Associação Brasileira de Divulgação Científica, 2014)
Cocaine sensitization is a marker for some facets of addiction, is greater in female rats, and may be influenced by their sex hormones. We compared the modulatory effects of endogenous or exogenous estradiol and progesterone on cocaine-induced behavioral sensitization in 106 female rats. Ovariectomized female rats received progesterone (0.5 mg/mL), estradiol (0.05 mg/mL), progesterone plus estradiol, or the oil vehicle. Sham-operated control females received oil. Control and acute subgroups received injections of saline, while the repeated group received cocaine (15 mg/kg, ip) for 8 days. After 10 days, the acute and repeated groups received a challenge dose of cocaine, after which locomotion and stereotypy were monitored. The estrous cycle phase was evaluated and blood was collected to verify hormone levels. Repeated cocaine treatment induced overall behavioral sensitization in female rats, with increased locomotion and stereotypies. In detailed analysis, ovariectomized rats showed no locomotor sensitization; however, the sensitization of stereotypies was maintained. Only females with endogenous estradiol and progesterone demonstrated increased locomotor activity after cocaine challenge. Estradiol replacement enhanced stereotyped behaviors after repeated cocaine administration. Cocaine sensitization of stereotyped behaviors in female rats was reduced after progesterone replacement, either alone or concomitant with estradiol. The behavioral responses (locomotion and stereotypy) to cocaine were affected differently, depending on whether the female hormones were of an endogenous or exogenous origin. Therefore, hormonal cycling appears to be an important factor in the sensitization of females. Although estradiol increases the risk of cocaine sensitization, progesterone warrants further study as a pharmacological treatment in the prevention of psychostimulant abuse.